Gestão participativa no processo operacional da John Deere - Montenegro/RS - Meneghine, Milena Pizzolotto de Conti (2009)
The present research is a study of case and offers a model which focuses on the effective participation of operational level collaborators in detecting flaws in the process through the Participative Management System. The study was carried out at John Deere Montenegro / RS, with the operational level collaborators and their managers. The Participative Management System is a means of getting to the causes and possible solutions of operational flaws, creating greater people s involvement at operational level in order to find an alternative and possibly efficient solution for the proposed problem. The research used was the descriptive through a quali-quantitative method. The execution of the study was carried out through bibliographical sources and analysis of evaluation protocols filled in by the collaborators and their managers. Based on the analysis, a Participative Management System was suggested in order for the Company to search for cooperation in mutual effort so as to make a better use of the collaborators potential in suggesting, participating, identifying and solving problems, and therefore aiming at reducing the operational flaws. It was suggested that, in future works, the proposed model is applied in a Company with the same line of business as John Deere s or even a remodeling of the system is done in order to adapt it to other Company trades and, in these cases, with an effective application of it. Moreover, statistical tools should also be applied so as to enable production comparisons before and after the changes in the management model.